Minimal benefit of earlier‐than‐recommended repeat colonoscopy among US Medicare enrollees following a negative colonoscopy. Issue 7 (14th August 2014) - Yang, Y.‐X.; French, B.; Localio, A. R.; Brensinger, C. M.; Lewis, J. D.
Summary Background A large proportion of US Medicare beneficiaries undergo earlier‐than‐recommended follow‐up colonoscopies after negative screening colonoscopy. Such practice entails substantial cost and added risk. Aims To compare the risk of colorectal cancer (CRC) associated with varying follow‐up colonoscopy intervals following a negative colonoscopy, and to determine whether the potential benefit of a shorter colonoscopy follow‐up interval would differ by gender. Methods We conducted a weighted cohort study using the Surveillance, Epidemiology and End Results‐Medicare linked database (1991–2006) among 932 370 Medicare enrollees who are representative of the entire US elderly population. We compared the cumulative incidence of CRC among patients who underwent follow‐up colonoscopies at different intervals following a negative colonoscopy. The primary outcome was incident CRC. Results The eligible study cohort (n = 480 864) included 106 924 patients who underwent ≥1 colonoscopy. Men were more likely to require polypectomy during their initial colonoscopy than women. Compared to the recommended 9–10 year follow‐up colonoscopy interval, an interval of 5–6 years was associated with the largest CRC cumulative risk reduction [i.e. 0.17% (95% CI: 0.009–0.32%)]. The magnitude of risk reduction associated with shorter colonoscopy follow‐up intervals was not significantly different between men and women. Conclusions Among elderly individuals who undergo a negative colonoscopy, the magnitude of reduction in the cumulative CRC risk afforded by earlier‐than‐recommended follow‐up colonoscopy is quite small, and probably cannot justify the risk and cost of increased colonoscopy frequency. In addition, there are insufficient differences between men and women to warrant gender‐specific recommendations.